Literature Review: TPACK-Based Science Learning in Supporting Teacher Quality in Indonesia (Lembaga Pengembangan Kinerja Dosen, 2022)
In the era of globalization, the world of education has made very significant progress in all fields. All have been based on the use of information and communication technology in the teaching and learning process. Technology acts as a tool to help students and teachers in conveying information more effectively. However, students have not been able to master technology-based learning materials. So, teachers must facilitate and monitor student performance so that they can more easily and quickly master the material. The professional quality of teachers in Indonesia is still relatively low. This is because the human resources of the Indonesian people are still lagging behind compared to other countries. The quality of teachers in Indonesia needs to be improved by using a learning approach. Learning approach based on Technology Pedagogical Content Knowledge (TPACK). This TPACK approach makes it easier for teachers to master technology that is by learning content so that students are motivated and active in learning. This study aims to determine TPACK-based learning in supporting the quality of teachers in Indonesia. This research uses the type of library research. Research samples from literature studies sourced from Google Scholar and Eric Journal. The criteria for the data to be sampled are articles published in 2015-2022. The data that was used as a sample amounted to 15 articles that were following the research variables. Data analysis is qualitative data analysis. The results show that from 15 articles that have been analyzed, TPACK-based science learning is very helpful for science teachers in Indonesia. TPACK-based science learning enhances the professionalism of teachers in teaching science material. Furthermore, the TPACK approach greatly helps teachers' professional performance to be more effective and efficient in mastering technology for learning facilities